Jurassic rifting to post‐rift subsidence analysis in the Central High Atlas and its relation to salt diapirism. (23rd December 2016) - Moragas, Mar; Vergés, Jaume; Saura, Eduard; Martín‐Martín, Juan‐Diego; Messager, Grégoire; Merino‐Tomé, Óscar; Suárez‐Ruiz, Isabel; Razin, Philippe; Grélaud, Carine; Malaval, Manon; Joussiaume, Rémi; Hunt, David William
Abstract: The subsidence evolution of the Tethyan Moroccan Atlas Basin, presently inverted as the Central High Atlas, is characterized by an Early Jurassic rifting episode, synchronous with salt diapirism of the Triassic evaporite‐bearing rocks. Two contrasting regions of the rift basin – with and without salt diapirism – are examined to assess the effect of salt tectonics in the evolution of subsidence patterns and stratigraphy. The Djebel Bou Dahar platform to basin system, located in the southern margin of the Atlas Basin, shows a Lower Jurassic record of normal faulting and lacks any evidence of salt diapirism. In contrast, the Tazoult ridge and adjacent Amezraï basin, located in the centre of the Atlas Basin, reveals spectacular Early Jurassic diapirism. In addition, we analyse alternative Central High Atlas post‐Middle Jurassic geohistories based on new thermal and burial models (GENEX ® 4.0.3 software), constrained by new vitrinite reflectance data from the Amezraï basin. The comparison of the new subsidence curves from the studied areas with published subsidence curves from the Moroccan Atlas, the Saharan Atlas (Algeria) and Tunisian Atlas show that fast subsidence peaks were diachronous along the strike, being younger towards the east from Early–Middle Jurassic to Late Cretaceous. This analysis also evidences a close relationship between these high subsidence rate episodes and salt diapirism.